Gamification Method Based on Information Communication Technology (ICT) in Islamic and Muhammadiyah Learning - Havidz Cahya Pratama; Zulfikar Yusuf; Farhah Pandu Agustin (At Turots: Jurnal Pendidikan Islam, 2025)
This study focuses on the gamification method based on Information Communication and Technology (ICT) in Muhammadiyah learning at SMK Muhammadiyah 1 Purbalingga, Purbalingga Regency. This study addresses the challenges faced in Muhammadiyah learning. The aim is to examine the application of ICT-based gamification methods in Muhammadiyah learning, especially through quizzes using the Kahoot and Quizizz applications. In addition, this study also evaluates the feasibility of learning media based on assessments from material experts, media experts, and students. This study uses a Research and Development (R&D) approach with qualitative and quantitative data collection techniques. Qualitative data were obtained through questionnaires containing explanations and suggestions from material experts and media experts. Quantitative data were collected using a Likert scale (5, 4, 3, 2, 1) which were then converted into qualitative data. Data collection instruments include questionnaires, interviews, and observations, with respondents consisting of material experts, media experts, and students. This study follows the eight stages of development from Sugiyono: (1) analysis of potential and problems identifying the needs and obstacles faced by students; (2) data collection from Muhammadiyah books, online sources, and learning modules; (3) product design in the form of interactive quizzes based on Kahoot and Quizizz; (4) product validation by material experts and media experts, which gave an average score of 85.5% (good category) for material validation and 92.7% (very good category) for media validation; (5) product revision based on expert advice; (6) product trials on class X Accounting 1 students, with an average score of 91.2% indicating a very good response from students regarding the attractiveness and ease of learning media; (7) further product revision; and (8) mass production, which resulted in an average response of 90.6% from class X students, indicating that this media is effective and able to increase student participation and understanding of Muhammadiyah material. The results of the study indicate that the ICT-based gamification method is effective in increasing student involvement, attracting interest in learning, and deepening student understanding of Muhammadiyah learning. This media is suitable for widespread application in technology-based learning.